Measures of Indigenous wellbeing and their determinants across the lifecourse (3rd lecture) - Biddle, Nicholas (My University, 2011)
Indigenous Australians report lower levels of physical health than the non-Indigenous population. At around 22 per cent, Indigenous Australians were around twice as likely to report that their health was either fair or poor compared to non-Indigenous Australians (ABS/Australian Institute of Health & Welfare (AIHW) 2010). Although Indigenous adults were found to be only slightly less likelyto have a long-term condition than non-Indigenous adults (based on analysis of the 2004–05 National Aboriginal and Torres Strait Islander Health Survey (NATSIHS)), the difference was much greater when the relatively young Indigenous age profile is taken into account. When age-standardised, Indigenous Australians in 2004–05 were 1.6 times as likely to report that they had asthma, 3.4 times as likely to report diabetes/high sugar levels and 10.0 times as likely to report a kidney disease.
Physical and mental health
2011 CAEPR Lecture Series
Keywords: Culture -- Indigenous; Health -- Access to services; Health and wellbeing; Health; Culture; Indigenous; Access to services; Health and wellbeing